Hexahydroquinoline-3-carbonitrile as Sustainable Corrosion Inhibitor for Mild Steel: Electrochemical and Surface Investigations - Thomas, Ashly; Aparna, E.P.; James, Jilly; Antony, Priya; Devaky, K.S. (Asian Journal of Chemistry, 2026)
A simple and eco-friendly microwave-assisted approach was applied to synthesise hexahydroquinoline-3-carbonitrile derivatives as corrosion inhibitors. The quinoline derivatives were obtained by reacting nitriles and chalcones with ammonium acetate under microwave irradiation. The synthesised hexahydroquinoline-3-carbonitriles were characterised using FT-IR, 1H NMR, 13C NMR, HRMS and SCXRD techniques. The efficiency of synthesised hexahydroquinoline-3-carbonitriles in inhibiting corrosion on mild steel was investigated using electrochemical methods (EIS and polarisation) and surface morphological analysis (AFM). According to EIS and polarization studies, hexahydroquinoline-3-carbonitriles act as mixed-type corrosion inhibitors by adsorbing at the metal/electrolyte interface and thereby preventing mild steel corrosion. The AFM analysis also confirmed that the hexahydroquinoline-3-carbonitriles were successfully adsorbed onto the surface of mild steel.